Duration of the phone call in wrong connection to 194 operator - Slavoljub (General Practice, 2023)
Introduction. Time is an essential category in the Emergency Department. The phone call duration, with the person who`s calling, should be optimal in order to make sound decisions. If the phone call is due to a wrong number it should be made as shorter as possible. Objective: We aimed to show how long the conversations with the caller lasted, for calls that were qualified as having the wrong connection. Method. We used the electronic phone call database (194/94) for 2009. The data were put in a spreadsheet (Excel table) where they were sorted and researched. Out of the total of 739.742 calls we singled out 93.393, which makes 12.62%, and they were classified as the wrong connection. Due to the great variability in the upper scale of the values we cut the base for 5% of the shortest and longest calls. After the database cut 84.053 calls remained. The phone call duration was measured from the moment the receiver was picked up to the moment the line was disconnected. Results. Analyzing 84.053 wrong connections we came up with these results: minimal phone call duration was 6 seconds and maximal 194 seconds, with mean value of 30.28 seconds. Discussion. The number of wrong connections is huge in Emergency Departments all around the world (fire brigades, police, medical emergency) but there are no valid data on the time spent on those calls. Conclusion. Phone calls with wrong connection last too long. Therefore, operators and callers should be well educated.